Faktor-Faktor yang Mempengaruhi Pemilihan Karier Menjadi Akuntan Publik di Universitas Muhadi Setiabudi - Ma’rifatul Indra Oktaviani; Yenny Ernitawati; Dumadi; Anisa Sains Kharisma; Maftukhin (Universitas Muhadi Setiabudi, 2021)
The purpose of this study is to find out whether professional training, work environment, and social values affect the perception of accounting students having a career as a public accountant. This research is included in the type of descriptive research with a quantitative approach. This primary data collection method was carried out using a questionnaire method that was distributed to respondents. The population in this study were employees who took accounting study programs at Muhadi Setiabudi University. The results of this study stated that partially the factors of professional training, work environment, and social values had a significant effect on career selection to become public accountants by employees who took accounting study programs at Muhadi Setiabudi University (UMUS). Simultaneously F-count is greater than F-table. The calculation shows that professional training, work environment, and social values together have a significant influence on the selection of a career as a public accountant by employees who take accounting study programs at Muhadi Setiabudi University or in other words, the hypothesis is accepted.